1997
DOI: 10.1148/radiology.203.2.9114089
|View full text |Cite
|
Sign up to set email alerts
|

Airway obstruction in asthmatic and healthy individuals: inspiratory and expiratory thin-section CT findings.

Abstract: Thin-section CT is of limited value in distinguishing asthmatic patients with normal airflow or mild airflow obstruction from healthy subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
1
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(84 citation statements)
references
References 0 publications
3
78
1
2
Order By: Relevance
“…According to these criteria, the prevalence of bronchial dilatation in asthmatic patients has been reported to be 3% to 66.7% (40,42). Bronchial dilation can also occur in healthy subjects, but the prevalence has been reported to be much lower than that in asthmatic subjects (28,30,41,43). Cylindrical bronchial dilation was reported to be the most common morphologic pattern identified on CT scans of asthmatics, mainly involved in segmental and distal bronchi, especially in the lower lobes (14,15,43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to these criteria, the prevalence of bronchial dilatation in asthmatic patients has been reported to be 3% to 66.7% (40,42). Bronchial dilation can also occur in healthy subjects, but the prevalence has been reported to be much lower than that in asthmatic subjects (28,30,41,43). Cylindrical bronchial dilation was reported to be the most common morphologic pattern identified on CT scans of asthmatics, mainly involved in segmental and distal bronchi, especially in the lower lobes (14,15,43).…”
Section: Discussionmentioning
confidence: 99%
“…Bronchial dilation was considered if the internal diameter of any bronchi was greater than that of the adjacent pulmonary artery, the bronchial lumina (distal to bifurcation) had a lack of tapering and was greater than 2 cm, or if the peripheral airways (within 1 cm of the costal pleura) was visible ( Figure 2) (15,28,31,32). Bronchial dilation were divided into three types according to the morphology of bronchi: (I) cylindric bronchial dilation, defined as the lack of bronchial tapering or the presence of smooth bronchial dilatation, and bronchial lumen greater than that of the accompanying pulmonary artery ( Figure 2A,B); (II) varicose bronchial dilation, identified when irregular or beaded dilatation of the bronchus were recognized ( Figure 2B,C); and (III) cystic bronchial dilation, diagnosed by presence of evident strings or clusters of cysts (15,33,34).…”
Section: Assessment Of Bronchial Dilationmentioning
confidence: 99%
“…The frequency with which air-trapping is identified on HRCT increases with age as does the extent, which is also influenced by cigarette smoking [17,109]. A relatively high prevalence of mosaic pattern has been reported in a study of 14 healthy subjects and 39 asthmatic individuals; a mosaic pattern was seen with equal frequency in both groups (21% and 18%) [110]. In addition, trivial extents of airtrapping on expiratory CT occurred with similar frequency in both groups (54% and 49%), whereas severe air-trapping was seen much less frequently in healthy subjects than asthmatics (14% versus 50%).…”
Section: Accuracy Of High-resolution Computed Tomography Signs and Inmentioning
confidence: 95%
“…BEIGELMAN-AUBRY et al [70] demonstrated a lower baseline airway lumen area in asthmatics compared with controls pre-bronchodilator, but the difference was abolished after salbutamol. In addition, the airway lumen diameter to arterial diameter ratio has been reported to be lower in asthmatic patients with a forced expiratory volume in one second (FEV1) ,60% (mean¡SD 0.48¡0.11) compared with control subjects (0.65¡0.16) and asthmatics who had normal or slightly decreased FEV1 values (0.60¡0.16 and 0.60¡0.18, respectively) [71]. Conversely, NIIMI et al [72] found no decrease in lumen area in the right apical upper lobe bronchus in asthmatics, irrespective of disease severity, compared with a normal group.…”
Section: Airway Imaging In Asthma Airway Dimensionsmentioning
confidence: 99%